Design and testing of a centralized protection scheme for micro-grids - Mirsaeidi, Sohrab (2015)
Micro-grids comprise low voltage distribution systems with distributed energy resources (DERs) and controllable loads which can operate connected to the medium voltage grid or islanded in a controlled coordinated way. This concept aims to move from “connect and forget” philosophy towards a full integration of DERs. Micro-grids can provide numerous economic and environmental benefits for end-customers, utilities and society. However, their implementation poses great technical challenges, such as a new philosophy in design of protection systems. In this work, a micro-grid protection scheme is presented based on positive-sequence component using phasor measurement units (PMUs) and a central protection unit (CPU). The salient feature of the proposed scheme in comparison with the previous works is that it has the ability to protect both radial and looped micro-grids against different types of faults with the capability of single-phase tripping. Furthermore, since the CPU is capable of updating its pickup values (upstream and downstream equivalent positive-sequence impedances of each line) after the first change in the micro-grid configuration (such as transferring from grid-connected to islanded mode and or disconnection of a line, bus, or DER either in grid-connected mode or in islanded mode), it can protect micro-grid against subsequent faults. Finally, in order to verify the effectiveness of the suggested scheme and the CPU, several simulations have been undertaken by using DIgSILENT PowerFactory and MATLAB software packages.